THE EVOLUTIONARY ORIGINS OF IDIOMS: TRACING THE HISTORICAL ROOTS OF COMMON PHRASES: 1-SON 2-TO’PLAM IYUL 2023 yil - Student of English Philology, Karakalpak State University, UZBEKISTAN, Kokanova N.J (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Idioms, a unique and colorful aspect of human language, are expressions or phrases that carry a figurative meaning beyond their literal interpretation. They have become an integral part of our everyday communication, but their evolutionary origins and historical roots remain largely unexplored